Analysis Of The Current State Of Technology Entrepreneurship In Russia And Abroad - Kamilevna Amerhanova, Alsu (2017)
The paper presents the current state of innovative entrepreneurship in Russia and foreign countries, which occupies a significant share in the creation of GDP in the economies of developed countries, and also attracts researchers from different countries due to the lack of a unified theory of technological entrepreneurship. One of the reasons which prevent raising the level of innovation in the Russian economy is a low level of activity of technological entrepreneurship entities. Features of technological entrepreneurship predetermine the need to develop measures of regulation, financing, etc. adapted to its specifics. The influence of macroeconomic dynamics on the development of innovative entrepreneurship in Russia is shown, and a comparative analysis of innovative entrepreneurship in Russia and the European Union as an example of developed economies is conducted. The presence of cultural and behavioral barriers to the further development of technological entrepreneurship in Russia is revealed, a conclusion is made about the decisive influence of macroeconomic dynamics and the steady development of the institutional environment for the implementation of technological innovation by small businesses.